MAKANAN PENDAMPING ASI - Yulia Safitri (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
The research objective was to determine the relationship of knowledge to the mother's attitude in providing complementary feeding in the village health center field weeds.This is a descriptive analytic study with cross sectional design. The sample was selected by simple random sampling of all mothers with babies aged 6-12 months who are 32 or older people. Primary data were collected using interviews and observation. The results showed that the relatively good knowledge of the respondents (56.2%), the attitude of the respondents classified as moderate (65.6%). There is a significant relationship between knowledge by providing complementary feeding (0.001), and significant relationship between attitudes to the provision of complementary feeding (0.001). It is recommended to health workers to be more routine counseling to mothers who have babies and approach local community leaders in order to help doing the counseling.